An Analytical Investigation Of The Concept Of Pratyahara In The Yoga Upanishads. - S, Ashok; K, Ramesh Babu (International Journal of Psychosocial Rehabilitation, 2020)
Pratyahara, a pivotal component of the eight limbs of yoga, represents the withdrawal of the senses from external distractions, creating a bridge between the physical and mental aspects of yoga practice. This abstract provides an overview of an analytical investigation into the profound concept of Pratyahara as elucidated in the Yoga Upanishads. Drawing on a range of ancient texts, this research delves into the historical and philosophical underpinnings of Pratyahara, unveils its techniques, and explores its contemporary relevance. By employing a multifaceted approach, including textual analysis, historical context, and practical application, this study unveils the multifaceted dimensions of Pratyahara, offering a comprehensive understanding of its evolution and significance within the yogic tradition. As a result, this research contributes to the deeper comprehension and integration of Pratyahara into modern yoga and mindfulness practices, fostering a bridge between ancient wisdom and present-day well-being.